Strategi Pengasuhan Anak Usia Dini di Era Teknologi Dengan Berbasis Literasi Digital - Sari, Novita; Kadafiah, Siti; Nurhayati, Nurhayati; Gusniati, Gusniati; Purwaningrum, Purwaningrum; Sari, Rahayu Yunita; Safira, Ratu Sella; Umah, Khaerul; Daniati, Daniati; Ikromah, Ikromah; Putihat, Iip; Isnawati, Isnawati (Universitas Pahlawan Tuanku Tambusai, 2025)
The development of digital technology provides significant opportunities for children to gain new learning experiences, but also presents challenges in parenting. Parents are required to have adequate digital literacy to be able to guide their children wisely in using technology. This Community Service Program (PKM) aims to formulate digital literacy-based early childhood parenting strategies through focus group discussions (FGDs) with parents. Participants included parents who discussed perceptions, obstacles, and practices of digital parenting. The FGD results indicated that most parents recognize the benefits of technology as an educational medium, but face obstacles in implementing digital controls, such as limited understanding of parental control features and difficulty managing screen time. Good practices that emerged included implementing device use schedules, selecting educational apps, and active parental involvement when children use digital media. Effective parenting strategies in the technology era must integrate active mentoring, implementing rules for digital media use, and strengthening parents' digital literacy capacity.